2022
DOI: 10.1136/heartjnl-2022-320939
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage preservation versus closure during surgical ablation of atrial fibrillation

Abstract: ObjectiveThere is limited evidence regarding the effectiveness of left atrial appendage (LAA) closure during surgical ablation of atrial fibrillation (AF) in yielding superior clinical outcomes. This study aimed to evaluate the association of LAA closure versus preservation with the risk of adverse clinical outcomes among patients undergoing surgical ablation during cardiac surgery.MethodsWe evaluated 1640 patients (aged 58.8±11.5 years, 898 women) undergoing surgical ablation during cardiac surgery (including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Ando et al [32] performed a meta-analysis using 7 research articles including almost 3900 patients and observed that LAAO was associated with lower mortality and decreased risk of cerebral vascular accident (CVA) in patients with AF, while a metaanalysis by Tsai et al [33] including 3653 patients showed decreased incidence of stroke and all-cause mortality in the LAAO group. Two large retrospective cohort studies by Lee et al [34] and Kim et al [35] did not demonstrate long-term benefit of LAAO without ablation. The present study demonstrated a lower rate of long-term stroke within the group who underwent LAAO without ablation in comparison to the group that underwent neither ablation nor LAAO.…”
Section: Discussionmentioning
confidence: 93%
“…Ando et al [32] performed a meta-analysis using 7 research articles including almost 3900 patients and observed that LAAO was associated with lower mortality and decreased risk of cerebral vascular accident (CVA) in patients with AF, while a metaanalysis by Tsai et al [33] including 3653 patients showed decreased incidence of stroke and all-cause mortality in the LAAO group. Two large retrospective cohort studies by Lee et al [34] and Kim et al [35] did not demonstrate long-term benefit of LAAO without ablation. The present study demonstrated a lower rate of long-term stroke within the group who underwent LAAO without ablation in comparison to the group that underwent neither ablation nor LAAO.…”
Section: Discussionmentioning
confidence: 93%
“…Our data revealed that younger patients had smaller atria, which could be a protective factor. And only the older population (21.7%) had LA scars or Low-voltage areas on voltage maps, indicating LA strutural alterations and fibrosis, compared to the very young population, which all had normal voltage maps [20] . Secondly, in older patients, other poor ablation risk factors such as hypertension, obesity, and obstructive sleep apnea syndrome were higher.…”
Section: Discussionmentioning
confidence: 95%
“…However, more recent findings based on real-world evidence have reported conflicting results: in an observational study on 1640 patients who underwent cardiac surgery between 2001 and 2018, Kim et al [24] did not find a difference in the risk of stroke or mortality at 3.5…”
Section: Discussionmentioning
confidence: 98%